2013
DOI: 10.1039/c3ra40505b
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of Au@Pd/graphene nanostructures: electrocatalytic ethanol oxidation for direct alcohol fuel cells (DAFCs)

Abstract: Surfactant-free bimetallic Au@Pd core-shell NPs on graphene sheets were fabricated from Au, Pd ions and graphene oxide by one-step reduction using ascorbic acid as an eco-friendly reducing agent. Au@Pd NPs with about 7 nm size are evenly distributed on the surface of graphene. The core/shell structures were confirmed with X-ray diffraction (XRD) and High-angle annual dark field scanning transmission microscopy (HAADF-STEM) mapping analysis. Prepared Au@Pd/graphene nanocomposites show an excellent electrocataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…SHE) is higher than that of Pd(II) ( E 0 PdCl4 2− /Pd = +0.6 V vs . SHE) 35 . Therefore, Au(III) is preferentially reduced by microbial components and extracellular polymeric substance ( E 0 = −0.32 to −0.1 V vs .…”
Section: Discussionmentioning
confidence: 99%
“…SHE) is higher than that of Pd(II) ( E 0 PdCl4 2− /Pd = +0.6 V vs . SHE) 35 . Therefore, Au(III) is preferentially reduced by microbial components and extracellular polymeric substance ( E 0 = −0.32 to −0.1 V vs .…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Thus, Pd/Au composite nanoparticles (NPs) with bimetallic alloy and core-shell (CS) structures have been successfully developed to catalyze various electrochemical reactions. [5][6][7][8][9][10] However, they lead almost no real improvement in Pd catalysis performance as compared with Pd nanoparticles because these structures still rely on the exterior surfaces of Pd shells to perform the electrocatalysis, very similar to conventional Pd nanoparticles. Moreover, it is still expensive to utilize especially when the use of Au does not add any value in catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Recently, RGO and/or metal NPs have been synthesized using various green reducing agents such as sugar, wild carrot, ascorbic acid (AA) and amino acids etc. [14][15][16][17][18][19] Of these, AA shows excellent reduction activity on both the metal and graphene oxide. Earlier studies on the reduction reaction performed in an aqueous medium 14,15 revealed that AA has a strong affinity with the aqueous medium, resulting in the formation of metallic clusters, albeit with reduced catalytic activity.…”
mentioning
confidence: 99%